CURRENT SOCIAL NEEDS MUSIC THERAPY: वर्तमान समय की सामाजिक आवश्यक्ता संगीत चिकित्सा - Raj, Sadhana (International Journal of Research -GRANTHAALAYAH, 2015)
There is also a rich tradition of music in India. Few countries have found such an old and rich tradition of music. Indian music has an inspiring Siva and Saraswati which means that human beings cannot develop such high art without any divine inspiration, only on their own strength. Music existed in India since Vedic period. The Yajurveda mentions several instrumental choirs in the 19th and 20th mantras of the 30th scandal. Which makes the existence of music clear. The history of Indian music is at least 4000 years old. The most ancient music mentioned in the world is found in the Samaveda, the artistic atmosphere of various instruments and vocals developed here. Pythagoras became the first person in Europe to determine the place of vowels by the laws of mathematics. भारत में भी संगीत की समृद्ध परम्परा रही है। कुछ ही देशों में संगीत की इतनी पुरानी एवं समृद्ध परम्परा पायी गई है। भारतीय संगीत के प्रेरक षिव और सरस्वती है इसका तात्पर्य है कि मानव इतनी उच्च कला को बिना किसी दैवी प्रेरणा के, केवल स्वयं के बल पर विकसित नहीं कर सकता। वैदिककाल से ही संगीत भारत में विद्यमान था। यजुर्वेद में 30वें कांड के 19वें और 20वें मंत्र में कई वाद्य बजानेवालों का उल्लेख है। जिससे संगीत का अस्तित्व स्पष्ट होता है। भारतीय संगीत का इतिहास कम से कम 4000 वर्ष पुराना है। संसारभर में सबसे प्राचीन संगीत का उल्लेख सामवेद में मिलता है यहाँ विभिन्न प्रकार के वाद्य यंत्रों और स्वरों के कलात्मक वातावरण का विकास हुआ। यूरोप में पाइथागोरस पहला व्यक्ति हुआ है जिसमें गणित के नियमों द्वारा स्वरों के स्थान को निर्धारित किया।